The effect of a maximal stretch-shortening cycle fatigue workout on fast stretch-shortening cycle performance - Comyns, T. M.; Harrison, A. J.; Hennessy, L. K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study examined the effect of a maximal stretch-shortening cycle fatigue workout on the biomechanical performance of rebound jumps that were done 15, 45, 120 and 300 seconds post-fatigue. Thirteen elite level rugby players participated in the study. Rebound jumps were done before and after the workout. All jumps were performed on a sledge and force plate apparatus. Flight time, ground contact time, peak force and leg spring stiffness were the dependent variables. The results indicated that the fatigue workout significantly reduced flight time (p < 0.001), peak force (p < 0.01) and increased contact time (p < 0.05) at the 15 second interval. The efficiency of the stretch-shortening cycle function was reduced. The results also indicate a potentiation effect at the 300- second interval due to a significant increase in peak force and leg stiffness (p < 0.05).